ANALISIS TINGKAT KETANGGUHAN BENCANA KELURAHAN DI KOTA TERNATE (STUDI KASUS PANDEMI COVID 19) - Marwan, Marwan; Baksir, Abdurrachman; Jannati, Jannati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The purpose of this study was to determine the level of government readiness at the kelurahan level in Ternate City in dealing with disasters by taking samples from 10 kelurahan as representatives of 77 kelurahan. This research was conducted with a qualitative approach, the interactive model. The results of the study revealed that the resilience level of the 10 urban villages was still in the low category. This is because there are only 3 sub-districts that are in the medium category, 5 sub-districts, and even 2 have not been categorized. This finding reveals that the level of village resilience to disasters is in the low category contributing to the weak handling of the COVID-19 pandemic in the City of Ternate in their respective environments. As a result of the government's lack of planning and preparation in dealing with the fast-spreading epidemic, the handling is very slow. Even impressed. The lack of strong disaster management institutionalization for the wider community causes the level of public understanding of disaster management to be low so that the level of awareness and sympathy of the community towards other communities is also low. This condition encourages the emergence of public attitudes that are contrary to the protocol for handling the covid pandemic. Not having made disaster management one of the government's priorities, disaster management, including COVID-19, always seems slow